Sistem Informasi Penjualan Produk Pertanian pada Badan Usaha Milik Desa (BUMDES) Sinar Bulan - Fajrian Noor, Muhammad; Rahman, Nanang; Sofyar (Indonesian Journal of Applied Accounting and Finance, 2023)
Technological developments that are increasingly advanced and developing can be utilized to support human work, including in the government sector. One form of good government can be seen from the services provided to the public which have been carried out effectively and efficiently. In the business world, the role of information technology and reliable application programs is no longer in doubt in supporting the ability of business units to win business competition. BUMDes Sinar Bulan Village has several business units that have been developed, one of which is the sale of agricultural products, because almost all of the people of Sinar Bulan Village are farmers, so agricultural products can be used as an opportunity by the village government to increase BUMDes income. In terms of recording buying and selling transactions, it is still done manually and does not comply with the rules in the accounting application program, resulting in an ineffective and inefficient recording system. Therefore, this research aims to create a Sinar Bulan village-owned enterprise (BUMDES) application program for WEB-based sales of agricultural products.